High-resolution melting curve analysis of polymorphisms within CD58, CD226, HLA-G genes and association with multiple sclerosis susceptibility in a subset of Iranian population: a case–control study - Ghavimi, Reza; Alsahebfosoul, Fereshteh; Salehi, Rasoul; Kazemi, Mohammad; Etemadifar, Masoud; Zavaran Hosseini, Ahmad (Acta neurologica Belgica, 2020)
Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system with unknown etiology, which typically is manifested in early to middle adulthood. Recently, genome-wide association studies have identified susceptibility of immune-related genes to be involved in MS predisposition. The goal of the current study was to investigate the association of single nucleotide polymorphisms (SNP) with the immunologically related genes responsible for the disease, composed of CD58 (rs2300747 A>G), CD226 (rs763361 C>T), and HLA-G (rs1611715 A>C), with MS susceptibility. In this case–control study, a total of 200 patients suffering from relapsing-remitting multiple sclerosis and 200 healthy individuals were recruited. DNA was extracted from blood and then all subjects were genotyped for the polymorphism within mentioned genes by high-resolution melting (HRM) real-time PCR method. Statistical analyses were performed using SPSS software (version 20; SPSS, Chicago, IL, USA). Our finding showed that there are significant differences in genotype and allele frequencies between two groups regarding rs763361 ( P = 0.035, OR 0.64, CI 95% for C allele) and rs1611715 ( P = 0.038, OR 1.57, CI 95% for AA genotype) polymorphisms within CD226 and HLA-G genes, respectively. Concerning rs2300747 polymorphism on CD58 gene, no significant differences were found between cases and controls. In general, results from the current study indicate that CD226 and HLA-G, but not CD58 genetic polymorphisms are associated with increased risk of MS in Isfahan population similar to European populations. However, to elucidate how these SNPs contribute to MS pathogenesis, functional studies are needed.